Influence of Body Heat Loss on Temperature and Velocity Fields in a Whole-Body Cryotherapy Chamber - Elfahem, Rim; Bouchet, Bastien; Abbes, Boussad; Polidori, Guillaume; Beaumont, Fabien (Fluids, 2023)
This study aims to investigate the impact of body heat loss on the thermal and aerodynamic conditions in a whole-body cryotherapy chamber. The underlying hypothesis is that the heat generated by the human body alters the thermal and aerodynamic environment inside the cabin. A numerical study was conducted to test this hypothesis and analyze the thermodynamic exchanges between the human body and the cabin during a 3 min whole-body cryotherapy session. The computational fluid dynamics (CFD) approach was used to study the unsteady heat transfer between the human body and the interior of the cryotherapy cabin. A thermal boundary condition, based on a mathematical model developed from experimental data, was applied to simulate skin cooling kinetics over time. The post-processing of the 3D results, including temperature, velocity fields, and thermal flux maps at the body surface, provided insight into the thermo-convective mechanisms involved in a whole-body cryotherapy session. The study found that body heat loss significantly affects the temperature fields inside the cabin, leading to global modifications of the aeraulic and thermal conditions. These findings suggest that cryotherapy protocols may need to be adjusted or the cabin set temperature optimized to enhance the therapeutic benefits.
Keywords: computational fluid dynamics (CFD); extreme cold; human body; skin temperature; whole-body cryotherapy (WBC)